Gli eroi mitologici dei Romani nella Genealogia deorum ovvero l’umanesimo particolare di Giovanni Boccaccio - Babics, Zsófia (Verbum – Analecta Neolatina, 2005)
In this article, the author presents an interesting analysis of Boccaccio’s De Genealogia deorum. The current image of Boccaccio, based on Decameron, is revised by presenting his humanistic method of describing heroes of the ancient Rome, relying on mainly Christian authors in the interpretation.